ФІЛОСОФСЬКІ ОСНОВИ КОНЦЕПЦІЇ САМОАКТУАЛІЗАЦІЇ ОСОБИСТОСТІ А.МАСЛОУ –ЗАСНОВНИКА ГУМАНІСТИЧНОЇ ПСИХОЛОГІЇ - Матвєєв, В. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статті розглядаються філософські засади гуманістичної психології, засновником якої єА. Маслоу. Виявляються досягнення даної психологічної течії в порівнянні з психоаналізом та біхевіори-змом. Аналізуються переваги та недоліки концепції самоактуалізації А. Маслоу. Досліджується впливруху контркультури на гуманістичну психологію.Матвеев В.А. Философские основы концепции самоактуализации личности А.Маслоу – осно-вателя гуманистической психологии. В статье рассматриваются философские основы гуманистиче-ской психологии, основателем которой является А. Маслоу. Выявляются достижения данного психоло-гического течения в сравнении с психоанализом и бихевиоризмом. Анализируются преимущества и не-достатки концепции самоактуализации А. Маслоу. Исследуется влияние движения контркультуры нагуманистическую психологию.Ключевые слова: гуманистическая психология, А. Маслоу, самоактуализация, психоанализ, бихе-виоризм, контркультура.Matveev V.A. The philosophical basics of concept of self-actualization personality of A.Maslow –the founder of humanistic psychology. The paper considers the philosophical foundations of humanisticpsychology, founded by A.Maslow,and ,where the main focus is on the research the problems of self-actualizationand self-realization of personality.Author of the article considers that predilection by eastern religious andphilosophical system in America in the second half of the twentieth century could affect the development ofhumanistic psychology. Defined achievements of humanistic psychology in comparison with psychoanalysis andbehaviorism, as in humanistic psychology, man is regarded as an active conscious person who is able to realizetheir creative potential, moving in the direction of personal growth.Author of the article considers by the specialachievement of this psychological movements that current theories of Maslow was confirmed in practicefirst ofall, in the company of «Non-Linear Systems», on the basis of an experiment in 1962h.In this article, humanisticpsychology compares with existentialism because there, and there the basis is the principle of realizing of theuniqueness own being and responsibility for own actions .In this article, humanistic psychology compared withexistentialism because there, and there it is based on the principle of the uniqueness of own being andresponsibility for own actions. Analyzing Maslow's Hierarchy of Needs, author of the article expresses hisdisagreement about the status of founder of humanistic psychology,that if the needs of the lower level will nolonger satisfied then the person should go back to this level, and gives examples when satisfaction of abilities cango from top to bottom - from the spiritual to the material.Analyzes аdvantages and disadvantages of the conceptof self-actualization A. Maslow. Investigates the influence of the counterculture movement on humanisticpsychology.Keywords: humanistic psychology, A.Maslow, self-actualization, psychoanalysis, behaviorism,counterculture.